2010
DOI: 10.1007/s12011-010-8653-x
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of l-Selenomethionine and Selenite in Rat Gut Contents

Abstract: L-selenomethionine (SeMet) and sodium selenite are widely used selenium nutritional supplements with potential benefit in preventing cancer. However, supplementation is not without risks of toxicity if intake is too high. The aim of the present study was to investigate SeMet and selenite metabolism in the gastrointestinal tract with particular focus on the formation of the volatile selenium excretion products, dimethylselenide (DMSe) and dimethyldiselenide (DMDSe). Adult male Wistar rats (n = 5) were euthanize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 36 publications
1
25
0
8
Order By: Relevance
“…Receiving selenium as selenomethionine, the chief natural nutritional form present in grain crops is better than sodium selenite as a source (Schrauzer & Surai 2009). Selenomethionine and sodium selenite have risks of toxicity if intake is too high (Krittaphol et al 2010). Therefore, the general population should be warned against the employment of selenium supplements for prevention of hepatopathies, cardiovascular or cancer diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receiving selenium as selenomethionine, the chief natural nutritional form present in grain crops is better than sodium selenite as a source (Schrauzer & Surai 2009). Selenomethionine and sodium selenite have risks of toxicity if intake is too high (Krittaphol et al 2010). Therefore, the general population should be warned against the employment of selenium supplements for prevention of hepatopathies, cardiovascular or cancer diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of selenium supplementation are still uncertain, and their indiscriminate use could generate an increased risk of toxicity (Miguel & Carmen 2008). Although the gut microbiota contributes to the excretion of excess selenium through the production of methylated selenium compounds and elemental selenium (Krittaphol et al 2010), the high doses of this element are highly toxic.…”
Section: Introductionmentioning
confidence: 99%
“…Selenite was analyzed by hydride generation atomic absorption spectrometry (HGAAS) [17,18] and DMSe and DMDSe by gas chromatography-mass spectrometry [8,19] as described elsewhere [4]. Serum selenium was determined by graphite furnace atomic absorption spectrometry based on a modification of the method of Jacobson and Lockitch [20].…”
Section: Methodsmentioning
confidence: 99%
“…Plasma selenium levels are low in patients with certain gastrointestinal disorders indicating a role for the gut microbiota in selenium disposition [2,3]. We previously showed that metabolism of SeMet and selenite in rat gut contents from normal rats [4] is similar to that mediated by microbial cultures (whole-cell suspensions of Enterobacter cloacae SLD, Escherichia coli or Pseudomonas syringae) in vitro [5,6]. Reported products of selenium metabolism include the volatile dimethylselenide (DMSe) and dimethyldiselenide (DMDSe) as well as elemental selenium [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation